Roles of functional amyloids in biofilms - Lipke, Peter (Henry Stewart Talks, 2023)
Biofilms, Amyloids, Bacterial biofilms, Biofilm cohesion, Fungal biofilms, Shear detection and response, Fungal amyloid adhesins